DIGITAL TAX TRANSFORMATION: CORETAX AND EASE OF USE ON TAXPAYER COMPLIANCE WITH TAX SOCIALIZATION AS A MODERATING VARIABLE - Suryanih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Digital tax transformation through Coretax is expected to improve administrative efficiency and taxpayer compliance. However, the effectiveness of its implementation still depends on user perception and the quality of socialization. This study aims to analyze the influence of Coretax and the perceived ease of use of the Coretax system on taxpayer compliance and examine the role of tax socialization as a moderating variable. The analysis was conducted using Moderated Regression Analysis (MRA) on 150 taxpayer respondents. The instrument test results showed that all items were valid and reliable, and the regression model met classical assumptions. The research findings indicate that Coretax and perceived ease of use have a positive and significant effect on taxpayer compliance. However, tax socialization was not proven to moderate the relationship between these two variables and taxpayer compliance. These results confirm that the success of tax digitalization is more influenced by system quality and perceived ease of use, while socialization requires a more effective approach to have a meaningful impact.